2007
DOI: 10.2174/138920007780866834
|View full text |Cite
|
Sign up to set email alerts
|

Presystemic Metabolism of Orally Administered Peptide Drugs and Strategies to Overcome It

Abstract: To date, the majority of therapeutic peptides and proteins have to be administered via parenteral routes, which are painful and inconvenient. Consequently, "injectable-to-oral-conversions" are highly on demand. Apart from a poor membrane uptake, however, an extensive presystemic metabolism of orally given peptide drugs is responsible for a comparatively very poor oral bioavailability. This presystemic metabolism in the gastrointestinal tract is based on luminally secreted enzymes (I) including pepsins, trypsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…5. Although the present study is not aimed at optimizing the metabolic stability, approaches are available to the medicinal chemist to increase the metabolic resistance against degradation as described recently (Bernkop-Schnü rch and Schmitz, 2007). Acylation of the N-terminal amine, for example, may increase the stability toward aminopeptidase B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5. Although the present study is not aimed at optimizing the metabolic stability, approaches are available to the medicinal chemist to increase the metabolic resistance against degradation as described recently (Bernkop-Schnü rch and Schmitz, 2007). Acylation of the N-terminal amine, for example, may increase the stability toward aminopeptidase B.…”
Section: Discussionmentioning
confidence: 99%
“…If it is revealed that a specific enzyme is responsible for the bulk of the degradation, then inhibitors such as pepstatin, bestatin, leupeptin, and chymostatin can be coadministered to deal with the specific enzymes. Several problems can arise from this type of inhibitor coadministration though, and it is not a general solution acceptable in the pharmaceutical field (Bernkop-Schnü rch and Schmitz, 2007). Maintaining the tripeptide sequence is a strategy to minimize the interactions with peripheral binding pockets on the main proteolytic enzymes, and a continued focus on arginine and tryptophan analogs may actually prove to be the simplest approach.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may involve factors which account for gender-related pharmacokinetic differences. Furthermore, the fact that orally the MEPG presents an LD50 above 3000 mg/kg may be due to difference in route of entry, which allows the drug to undergo presystemic metabolism before reaching the target tissue [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Brush border membrane of intestinal mucosal cells contains a peptide carrier system with rather broad substrate specificity and various endo-and exopeptidase activities (Bai and Amidon, 1992;Bernkop-Schnürch and Schmitz, 2007). Similar membrane-bound enzymes might be responsible for the transport and the degradation of degarelix.…”
Section: Discussionmentioning
confidence: 99%